2015
DOI: 10.1093/annonc/mdu496
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel plus oxaliplatin with or without fluorouracil or capecitabine in metastatic or locally recurrent gastric cancer: a randomized phase II study

Abstract: These results suggest that TEF is worthy of evaluation as an arm in a phase III trial or as a backbone regimen for new targeted agents in advanced GC. CLINICALTRIALS.GOV: Identifier Trial registration number: NCT00382720.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 22 publications
3
83
0
3
Order By: Relevance
“…In addition, a recent study has reported that combination chemotherapy comprising docetaxel (60 mg/m (from 14 to 7 days) plus docetaxel and oxaliplatin offered comparable efficacy against advanced gastric cancer with tolerable side-effects. In the present study, the effective rate of the DOX regimen was 75%, an outcome similar to that of earlier clinical trials using these drug combinations (23)(24)(25)(26), in which the median time to progression and median OS were not inferior to those achieved by the DCF regimen. However, overall clinical outcome for patients treated with the DOX regimen determined by the present study should be evaluated in a phase-II trial to compare it with that for patients treated with other DOX regimens or the conventional DCF regimen.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, a recent study has reported that combination chemotherapy comprising docetaxel (60 mg/m (from 14 to 7 days) plus docetaxel and oxaliplatin offered comparable efficacy against advanced gastric cancer with tolerable side-effects. In the present study, the effective rate of the DOX regimen was 75%, an outcome similar to that of earlier clinical trials using these drug combinations (23)(24)(25)(26), in which the median time to progression and median OS were not inferior to those achieved by the DCF regimen. However, overall clinical outcome for patients treated with the DOX regimen determined by the present study should be evaluated in a phase-II trial to compare it with that for patients treated with other DOX regimens or the conventional DCF regimen.…”
Section: Discussionsupporting
confidence: 89%
“…The FLOT regimen (fluorouracil, leucovorin, oxaliplatin and docetaxel) resulted in a median PFS of 5.1 months and a median OS of 11 months in a small non-randomised study [63]. An almost identical regimen used in a randomised phase II trial resulted in encouraging median PFS and OS of 7.7 and 14.6 months, respectively [II, B] [64]. As an alternative to platinum-based therapy, irinotecan plus leucovorin and infusional 5-FU (FOLFIRI) has been studied in both phase II trials and one phase III randomised trial in the first-line setting, and may be considered for selected patients [60,65].…”
Section: Perioperative Chemotherapymentioning
confidence: 99%
“…It showed that median OS of DCF was significantly longer than CF (9.2 months vs. 8.6 months; P = 0.02), but DCF produced more toxicity [38,39] . Several modified DCF regimens demonstrated the efficacy and the safety [40][41][42] . Thus, the original DCF is not recommended, and modified DCF is still one of the option in specific cases.…”
Section: First Line Therapymentioning
confidence: 99%